Efforts to Improve Reading Skills Through Big Book Media for Muhammadiyah Kepong Malaysia Guidance Students : Upaya Meningkatan Keterampilan Membaca Melalui Media Bigbook pada Siswa Bimbingan Muhammadiyah Kepong Malaysia - Maulinda Maulinda; Dewi Kesuma Nasution (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to determine efforts to improve reading skills in students of Guidance Muhammadiyah Kepong, Malaysia, through the use of Bigbook media. Bigbook media is a learning method that integrates visual and text elements effectively, so it is expected to increase student's interest and reading skills. This study was conducted using the classroom action research (CAR) method, which aims to improve the quality of learning through direct action in the classroom. The subjects of this study were 22 students involved in learning activities in the classroom that were used as research objects. These students became part of the experiment or action taken by the researcher to overcome problems in the teaching and learning process. This study was conducted in several cycles, each consisting of the planning stage, action implementation, observation, and reflection. The study results showed a significant increase in students' mastery of reading skills after applying big-book media. At the pre-action stage, most students were in the less category with a percentage of 45.45%, but after the application of KCB in Cycle I, there was an increase with an average percentage of 64%. Further improvement was recorded in Cycle II, where all students were in the very good category, with an average percentage of 86.4%. In addition, the assessment of student responses to the mastery of reading skills through the use of book media showed that the use of this media was very good in improving student mastery, with a percentage of mastery reaching 94%. Thus, the use of Bigbook Media is very good in improving the mastery of reading skills of Bimbingan Kepong Malaysia students.